Human rights, an analysis in pandemic times – Philosophy of Law (Research, Society and Development, 2021)
When we work on the concept of Philosophy, we are faced with the study of human existence. In the Philosophy of Law, our object of reflection is Human Rights, so fundamental to the formation of the contemporary world and the creation of constitutions that seek to defend humanity. The Universal Declaration of Human Rights is an inspiring framework for principles that prioritize peace, citizenship and democracy in the world. During the COVID-19 pandemic, human rights became insurmountable and international norms forced governments to adopt measures to avoid threats to public health. Health is everyone's right, as is Education. The pandemic has brought to light the long lived reality. Health is everyone's right, but many Brazilians do not have access to treatments and medication. As well as education, an always current and pertinent problem, which faces major challenges to reach students who do not have technological instruments that understand what is necessary for remote classes, online or distance learning (computer, cell phone, internet).